(untitled) (Latakia University Journal -Engineering Sciences Series, 2018)
إن توظيف عدد من الهوائيات في طرفي الإرسال والاستقبال لتشكيل ما يعرف بأنظمة الهوائيات متعددة المداخل والمخارج MIMO أسهم بشكل كبير بتحسين وثوقية الإرسال وزيادة معدل نقل المعطيات. الأمر الذي جعل هذه الأنظمة تمثل العمود الفقري في عالم الاتصالات اللاسلكية للعقد الاخير، مما أفسح الطريق أمام تطوير وابتكار تقنيات كثيرة في هذا المجال، وهذا ما تتطلب العمل الدائم على تحليل أبرز هذه التقنيات ومقارنة أدائها. يتناول هذا البحث عدة تقنيات تعتمد أنظمة الـ MIMO ذات الحلقة المغلقة كالتقنية P-OSM التي تعمل على تعظيم المسافة الاقليدية الصغرى بين رموز الإشارة في طرف الاستقبال بهدف تخفيض معدل خطأ البت, كذلك التقنيتين X, Y Precoders اللتين تعملان على تحسين ربح التنويع لأنظمة الـ MIMO. يهدف البحث لدراسة وتحليل أداء التقنيات السابقة من حيث معدل خطأ البت ودرجة التعقيد ضمن ظروف التشغيل العملية لأنظمة الاتصالات اللاسلكية بوجود قناة راجعة محدودة من المستقبل للمرسل. أظهرت النتائج إمكانية التشغيل العملي لتقنية P-OSM بشكل أبسط مقارنة مع التقنيات الأخرى بسبب أدائها الجيد ودرجة تعقيدها المنخفضة. The employment of multiple antennas at the transmission and reception side for the formation of a MIMO system contributed significantly to improve the reliability of transmission and increase the data rate. In the last decade, this system represented the backbone of wireless communications which paved the way for the development of many techniques in this area. Therefore, there is a need to study the most important of these techniques and compare its performance analysis. This research deals with several closed-loop MIMO techniques : (P-OSM) which maximizes the minimum Euclidean distance in the received signal constellation in order to reduce the bit error rate, (X and Y Precoders) which improve the diversity gain of MIMO system. The aim is to study and analysis the performance of previous techniques in practical scenarios of wireless communication systems in the presence of limited feedback channel. The results shows the possibility of practical employment of the P-OSM technique in a simple way compared to other techniques due to its good performance and low complexity order.